Study of LDH Isoenzymes in Myocardial Infraction at Vidharbha Region (Central India) - Rakesh Kumar Jha; Pradip Jain; Ankita Khandolkar; Archana Dhok (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: A significant cause of morbidity and mortality worldwide is myocardial infarction (MI).Within the first few hours of the beginning of MI, the greatest risk of death occurs. Thus, for the effectivetreatment of patients with MI, early detection of cardiac ischemia is essential. Inappropriate diagnosis ofpatients with chest pain sometimes leads to improper admission, and vice versa, of patients without MI.Physical examination, precise ECG results and evaluation of cardiac biomarkers play an important rolein the early diagnosis of acute ischemia, in addition to clinical history. In the present analysis, the cardiacbiomarker lactate dehydrogenase released during a MI event is discussed in depth.Aim: We conducted a cross sectional study to examine the different levels of LDH isoenzymes in myocardialinfarction patients those admitted in cardiac care unit in SMHRC Nagpur.Material and Methods: The present study included 100 subjects of age group 30-80 years. Patients admittedto the coronary care unit at SMHRC & AVBRH between January 2020 and June 2020 was consideredeligible for the study. These guidelines ensured that sufficient blood samples were available and the criteriafor diagnosis were consistent. Lactate dehydrogenase isoenzyme was fractionated by agarose gel electrophoresis as described by Cawley and Eberhard. The stained slides were scanned on Chromoscan at 520 mixand the percentages of the fractions were quantitated.Results: The results obtained in the present study indicate that serum lactate dehydrogenase enzyme activityincreases 4-5 folds in the first 24-72 hours after the onset of clinical infarction with a peak on the second day.It then declines gradually towards the normal within two weeks. Thus, determination of total serum LDHis valuable if patients present themselves for clinical check up even after a week from the day of infarct.Although the contribution of myocardium to total serum lactate dehydrogenase is large, its interpretationbecomes difficult if the diseases of other organs such as liver, kidney, etc.Conclusion: In conclusion, the present data strongly support the use of Lactate dehydrogenase for thediagnosis of MI. Such a strategy should boost both the precision and sensitivity for myocardial infarctiondiagnosis.